2016 IEEE International Conference on Communications (ICC) 2016
DOI: 10.1109/icc.2016.7510818
|View full text |Cite
|
Sign up to set email alerts
|

Congestion control in the recursive InterNetworking Architecture (RINA)

Abstract: RINA, the Recursive InterNetwork Architecture, is a novel "back to basics" type approach to networking. The recursive nature of RINA calls for radically different approaches to how networking is performed. It shows great potential in many aspects, e.g. by simplifying management and providing better security. However, RINA has not been explored for congestion control yet. In this paper, we take first steps to investigate how congestion control can be performed in RINA, and demonstrate that it can be very effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…F 18 Performance Improvements: In addition to the above security features, RINA has some other important features which are all very appealing for IoT networks [31]. For example, through some research work 2 and international projects 3 , it has been shown that RINA can effectively improve the network performance in terms of throughput and delay without compromising security [4]. F 19 Complexity Reduction: Considering the number of protocols, required flows, and especially required distinct mechanisms, RINA networks can satisfy security requirements with less complexity than in the current Internet.…”
Section: Rina Security Featuresmentioning
confidence: 99%
See 4 more Smart Citations
“…F 18 Performance Improvements: In addition to the above security features, RINA has some other important features which are all very appealing for IoT networks [31]. For example, through some research work 2 and international projects 3 , it has been shown that RINA can effectively improve the network performance in terms of throughput and delay without compromising security [4]. F 19 Complexity Reduction: Considering the number of protocols, required flows, and especially required distinct mechanisms, RINA networks can satisfy security requirements with less complexity than in the current Internet.…”
Section: Rina Security Featuresmentioning
confidence: 99%
“…Rina also reduces the size of routing tables [12], [32], [33]. F 20 Arbitrary Arrangement: DIFs can be arranged/stacked arbitrarily to provide different operations such as PEPs, multipath routing, and in-network resource sharing without compromising security [4].…”
Section: Rina Security Featuresmentioning
confidence: 99%
See 3 more Smart Citations